Between Official Orthodoxy and Received Wisdom: Explaining Urban House Vacancies in Nigeria : - Onwuanyi, Ndubisi (Journal of African Real Estate Research, 2022)
Housing policies demonstrate the importance of shelter in the hierarchy of human needs. Therefore, Nigeria has a history of initiatives, handled by a ministry of housing, to stimulate housing production. However, recently expressed views by the housing minister suggest a new official thinking which, if officially embraced, could have undesirable implications for the sector. The views dispute the much mentioned 20 million-unit housing shortfall; deny the existence of any shortfall because of observed urban vacancies; suggest that all vacant houses are available for use and can be utilised for existent urban needs; and attribute rising urban housing demand exclusively to rural-urban migration. In this paper, these views are examined, particularly because Nigeria has ordinarily not been associated with housing sufficiency; Nigeria’s characteristic situation of rapidly rising rents suggest a supply insufficiency; every vacant house may not be available for occupation; and urban migration can also come from non-rural sources. Data for the study comes from the archives, received wisdom on the operations of the housing industry and empirical findings in housing economics. The findings reveal that a lack of data evidence is enough justification for the minster’s dismissal of the much mentioned 20 million-unit shortfall, but not the complete absence of a shortfall. The assertion that vacancies imply an oversupply is equally unsubstantiated by data and unsupported by received wisdom. Also the view that all vacancies imply availability is misplaced; and the claim that urban migration is entirely of rural origin disregards urban-urban migration. The conclusion is that the claims of an oversupply and absence of a housing shortfall are unfounded, particularly in the absence of data evidence, the same grounds for official dismissal of the 20 million-unit shortfall. The study recommends that the ministry should have a “rethink and understand the problem”, particularly how the housing market works.